Cross-national differences in consumer response to the framing of advertising messages: An exploratory comparison from central Europe - Orth,Ulrich; Koenig,Hal; Firbasova,Zuzana (European Journal of Marketing, 2007)
This study examines consumer response to positively versus negatively framed advertisements in four Central European countries. Different emotional, cognitive and attitudinal reactions to advertisements for food products were found with respondents in Croatia, the Czech Republic, Hungary and Poland. Testing a comprehensive structural equation model separately for each country revealed differences as well as similarities in how positively and negatively framed advertisements elicited the emotional dimensions downbeat, pleased and attentive, and affected consumer cognitions and attitudes. Across countries, the intertwined roles of emotions and cognitions in affecting consumer attitudinal response were generally confirmed, suggesting cross-cultural robustness of the underlying framework.
Keywords: Marketing